Monocytes as suitable carriers for dissemination of dengue viral infection. Issue 10 (October 2022) - Hwang, Eun-Ha; Hur, Gyeung Haeng; Koo, Bon-Sang; Oh, Hanseul; Kim, Green; Jung, Hoyin; Baek, Seung Ho; An, You Jung; Park, Jong-Hwan; Hong, Jung Joo
Abstract: Dengue viruses (DENVs) exploit monocytes and macrophages for tropism and replication, therefore, establishing a long-term reservoir. However, their roles in dengue pathogenesis remains unclear. Here, using the human monocytic cell line THP-1, human primary monocytes, and non-human primate models, we show that DENV-infected monocytes represent suitable carriers for circulatory viral dissemination. Monocyte-derived macrophages expressing M2 surface markers at the gene level efficiently replicated, while the productivity of monocyte replication was low. However, attachment of DENVs to the cellular surface of monocytes was similar to that of macrophages. Furthermore, after differentiation with type-2 cytokines, DENV-attached monocytes could replicate DENVs. Productive DENV infection was confirmed by intravenous injection of DENVs into nonhuman primate model, in which, DENV attachment to monocytes was positively correlated with viremia. These results provide insight into the role of circulating monocytes in DENV infection, suggesting that monocytes directly assist in DENV dissemination and replication during viremia and could be applied to design antiviral intervention. Abstract : Monocytes; Dengue virus; Viral replication; Macrophage; Dengue pathogenesis.